Adsorption Ability for Toxic Chromium (VI) Ions in Aqueous Solution of Some Modified Oyster Shell Types - Thuy Chinh Nguyen; Xuan Thai Nguyen; Do Mai Trang Tran; Quoc Trung Vu; Van Hai Nguyen; Duy Trinh Nguyen; Minh Thanh Do; Thi Len Nguyen; Thi Ngoc Lien Ly; Hoang Thai (Bioinorganic Chemistry and Applications)
In this paper, the chromium, Cr (VI), ion adsorption ability of oyster shell samples collected from two sea regions in Vietnam (Phu Yen province and Quang Ninh province) was investigated and compared. The oyster shell samples were calcined at different temperatures and denatured by using ethylenediaminetetraacetic acid (EDTA). The Cr (VI) ion adsorption ability of the prismatic (PP) and nacreous (NP) shell layers of oysters was also evaluated. The characteristics of oyster shell samples before and after treatment were determined by using analysis methods including XRD, IR, BET, UV-Vis, and FESEM. The Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich models and fit statistic equations were used to study the adsorption isotherms of Cr (VI) ion adsorption by oyster shells. The Cr (VI) ions adsorption kinetic has been set up using four reaction models consisting of first-order, pseudo-first-order, second-order, and pseudo-second-order reaction models. Effects of experimental factors on the Cr (VI) ion adsorption process using oyster shells were also investigated and discussed in this work.